Management of Remuneration System Based on Performance for Lecturers and Employees at Islamic Higher Education as Public Service Agency - Huriyah, Lilik; Hsucheng Chiang, Tosti (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
Performance-based compensation or remuneration for lecturers and staff is crucial for realizing the higher education institution's vision and mission. However, many universities still compensate their lecturers and employees predominantly based on rank, position, and length of service. This study investigates the management aspects, including planning, implementation, and evaluation of a performance-based remuneration system for lecturers and staff at Islamic higher education institutions operating under a Public Service Agency, as well as the supporting and inhibiting factors. The research employs a descriptive qualitative approach. Data were collected through interviews, documentation, and observation. The study was conducted at the State Islamic University Sunan Ampel Surabaya, an Islamic university with Public Service Agency status. The findings indicate that the planning phase for the performance-based remuneration system at the State Islamic University Sunan Ampel Surabaya has been effectively executed. This planning includes issuing decrees from the Minister of Finance, the Rector's decree, establishing a remuneration team, formulating grading and position valuation, and socializing the performance-based remuneration system. Moreover, the implementation phase of this performance-based remuneration system has been carried out successfully, with payments made in subsequent periods. The Internal Audit Unit manages the evaluation of the performance-based remuneration system. The theoretical implication of this study is that it supports the theory and strengthens several findings from previous research on performance-based remuneration system management in higher education. Meanwhile, the practical implication of this study is that it can serve as a guideline in determining the grading of a remuneration system.